Pre-equilibrium excitation of nuclei in ([rho], [alpha]) and ([rho], 3He) reactions induced by 120, 160 and 200 MeV protons - Arendse, Gillian John (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.